(untitled) (Interdisciplinary Studies Journal, 2025)
This dossier brings together a collection of reflections on the contemporary intersections between culture and politics, with an emphasis on the impacts of digitalization, cyberculture, and new forms of sociability and activism emerging in the context of digital media. The many facets of contemporary life—traversed by the nuances of labor, technology, culture, and politics—give a unique brilliance to the proposed essays. This work is the result of a collective effort by students from the Federal University of Mato Grosso (UFMT) and the State University of Mato Grosso (Unemat), in collaboration with researchers from various Brazilian institutions, consolidating a critical, interdisciplinary production deeply committed to our time. With affection and gratitude, we extend a special thanks to Professor Dr. Mauricio Aurellano Nucamendi, from Mexico, whose participation in our course was pivotal to the reflections that make up this volume. His profound and sensitive lecture immersed us in discussions on politics, social development, and gender issues with rare depth — it was, without a doubt, the most striking moment of the entire formative experience. His gesture of international dialogue, between the Global South and our Brazilian public universities, continues to resonate in each of the texts presented here. The general objective of the collection is to foster debates on topics such as digital citizenship, cyberspace, digital culture, and cyberactivism. In doing so, it also challenges the role of technologies and discourses in the construction of identities, in the production of resistances, and in the struggle for narratives in the public space. Among the specific objectives, we highlight:a) To elucidate concepts such as culture, belonging, stereotypes, and symbolic commodification, also investigating processes of transculturation, counterculture, and resistance from the peripheries;b) To discuss digital culture and media processes on contemporary platforms;c) To reflect on space-time compression, digital convergence, and the accelerated temporality of social networks. Comprising 16 articles, the dossier organizes multiple perspectives and intellectual trajectories, presenting both theoretical analyses and empirical investigations. What the texts share is the desire to understand—and at times critically intervene in—the cultural and political dynamics that shape our present. We understand that proposing a dossier anchored in culture and politics—distinct fields within the mosaic of the social sciences—means daring to break paradigms and engage in plural dialogues among different theoretical perspectives without losing the critical essence that drives us. Each article shines with its own light, yet remains in harmony with the beacon of the collection. This is a dossier written by many minds and hands that confront material reality without losing tenderness and irreverence amid the rigor of academic writing.